Suicide and Risk Behaviors in an Incarcerated American Indian Population in the Northern Plains (United States), 1999-2000 - Severson, Margaret ([Verlag nicht ermittelbar], 2004)
This study was initiated by the administrator of a county jail in the Northern Plains of the United States who was concerned about the incidence of suicide behaviors in that facility, particularly among the American Indian population. It was a two-year project designed to evaluate the existing admissions suicide screening tool and to improve the instrument's cultural relevance for the American Indian population. The existing screening instrument used in the county jail to interview inmates at their intake was developed in New York. The main objective of the first year of the project was to determine if that instrument was culturally appropriate for the jailed American Indian population. The principal objective of the second year of the project was to determine whether the employment of different suicide screening protocols would make a difference in the responses of new detainees with regard to the likelihood of securing their honest reports of experiencing suicide ideation and its associated risk factors. For the duration of the project, all male and female inmates aged 18 and older who were booked into the jail went through the customary booking procedure that included the administration of the New York Suicide Prevention Screening Guidelines. In the first year of the project, researchers also administered a short self-report survey consisting of measures commonly associated with suicidal ideation. The self-report survey measured stress, anxiety, suicide ideation, hopelessness, and suicidal behavior history. The protocols in the second year of the project reflected efforts to test different screening conditions for four experimental groups and one control group of new detainees. The outcome variables of the short self-report survey consisted of measures of demographics, comfort experience during booking and the screening process, self-efficacy and management of depression, knowledge of mental health support available within the jail, and general well-being. In addition to the quantitative data collection, qualitative data were also collected to develop a straightforward assessment of suicide ideation criteria in this specific jail setting using semi-structured focus group interviews.